2001
DOI: 10.1068/p3178
|View full text |Cite
|
Sign up to set email alerts
|

A Prior for Global Convexity in Local Shape-from-Shading

Abstract: To solve the ill-posed problem of shape-from-shading, the visual system often relies on prior assumptions such as illumination from above or viewpoint from above. Here we demonstrate that a third prior assumption is used--namely that the surface is globally convex. We use complex surface shapes that are realistically rendered with computer graphics, and we find that performance in a local-shape-discrimination task is significantly higher when the shapes are globally convex than when they are globally concave. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 18 publications
(15 reference statements)
7
87
0
2
Order By: Relevance
“…We found that observers' interpretations were systematically biased (difference from 50%, p Ͻ 10 Ϫ5 , bootstrap significance test, 20,000 iterations), with a zero disparity Mach card reported as convex (66%) more frequently than concave (34%). Consistent with previous reports (Langer and Bülthoff, 2001;Liu and Todd, 2004), this suggests that observers have a bias for convex shape interpretations. By adding binocular disparity to the Mach card stimulus, we changed the perceived 3D shape systematically (Fig.…”
Section: Fmri Selective Adaptation For the Ambiguous Mach Card Stimulussupporting
confidence: 81%
“…We found that observers' interpretations were systematically biased (difference from 50%, p Ͻ 10 Ϫ5 , bootstrap significance test, 20,000 iterations), with a zero disparity Mach card reported as convex (66%) more frequently than concave (34%). Consistent with previous reports (Langer and Bülthoff, 2001;Liu and Todd, 2004), this suggests that observers have a bias for convex shape interpretations. By adding binocular disparity to the Mach card stimulus, we changed the perceived 3D shape systematically (Fig.…”
Section: Fmri Selective Adaptation For the Ambiguous Mach Card Stimulussupporting
confidence: 81%
“…It is interesting, for example, that the illusion is stronger for upright than for inverted faces (Hill & Bruce, 1993). Moving away from the special case of faces, Langer and Bülthoff (2001) tried to compare different assumptions about 3-D shape and concluded that the convexity assumption is as strong as two other assumptions: the viewpoint from above and the light from above (but see also van Doorn, Koenderink, & Wagemans, 2011;Wagemans, Van Doorn, & Koenderink, 2010). What is important for this review is that a bias for 3-D convexity over 3-D concavity does not imply an equivalent bias for 2-D convexity over 2-D concavity, because of the difference discussed earlier in how 2-D information is information about 3-D surface curvature-namely, the fact that a concave contour is not the projection of a concave surface.…”
Section: Questionmentioning
confidence: 99%
“…S4). By contrast, reversing the two eyes' views had no effect on the perceived depth structure for the unreliable portions of the shapes; instead, observers' judgments were consistent with the 3D shape specified by monocular shape cues in conjunction with a convexity prior (33,34). Thus, consistent with the use of intrinsic disparity markers, in locations where disparity signals are less reliable, observers' judgments of shape rely more on other sources of information about 3D shape.…”
Section: Discussionmentioning
confidence: 54%